Diagnostic Values of P-Wave Dispersion to Detect Diastolic Function in Patient with Hypertension - Braghmandaru Adhi Bhaskara; Rano Irmawan; Lucia Kris Dinarti; Hasanah Mumpuni (ACI (Acta Cardiologia Indonesiana), 2017)
Background: Hypertension is one of the main causes of cardiovascular disease. Patients with hypertension have increase risk of heart failure compared to populations with normal blood pressure. Clinical evidence shows diastolic dysfunction (DD) can lead to heart failure. Diagnostic of DD with echocardiography is important but access to echocardiography machines is limited compared to electrocardiography (ECG). ECG research correlates P-wave dispersion (PWD) with DD. The aim of this study is to determine the value of PWD to diagnose DD in patients with hypertension.Methods: A cross sectional study was conducted in patients with hypertension at Dr. Sardjito Hospital. Patients received echocardiography, ECG, blood pressure measurement and data recording. The diastolic dysfunction was determined based on 2016 ASE/EACVI criteria. We conducted ROC analysis to determine the cut-off point of P-wave dispersion and the area under the curve (AUC) value, and bivariate analysis on demographic and clinical factors related to PWD. Multivariate analysis was performed to determine the independent factors affecting PWD.Results: 113 patients met the criteria of the study subjects, with 47 men (37.2%), mean age 58.32±11.17 years. Thirteen (11.5%) subjects had DD and 37 subjects (32.7%) with increased PWD. Results showed increased PWD above 71.4 m.s with AUC 76.2%, sensitivity 75%, specifcity 72.2%, positive predictive value 33.3%, negative predictive value 96%, and accuracy of 72.5% in diagnosing DD.Conclusion: This is the frst study to examine the diagnostic value of PWD to detect diastolic function based on 2016 ASE/EACVI criteria. We found PWD above cut-off point 71.4 m.s has a moderate diagnostic value for detecting DD in patients with hypertension.